Using information technology - Williams, Brian K. (McGraw-Hill Companies, 2011)
The Williams, Using Information Technology, 9th edition utilizes a practical, applied approach to technology. This text is user-focused and has been highly updated including topics, pictures and examples. The Williams text contains less theory and more application to engage students who might be more familiar with technology. Continually published and updated for over 15 years, Using Information Technology was the first text to foresee and define the impact of digital convergence, the fusion of computers and communications. It was also the first text to acknowledge the new priorities imposed by the Internet and World Wide Web and bring discussion of them from late in the course to the beginning